A 20-80 MHz continuously tunable Gm-C low-pass filter for ultra-low power WBAN receiver front-end - Wang, Xiaoying (2022)
This paper presents a third-order Butterworth low-pass filter (LPF) with continuously tuning capability to be used in the receiver front-end for Wireless Body Area Network (WBAN). To realize the bandwidth tuning for multi-standard operation in WBAN receivers with ultra-low power consumption and minimized area, a novel transconductor-capacitor (Gm-C) filter is proposed. The proposed transconductor core uses an additional gain stage with regulated cascode structure to control the transconductance ( $G_{m}$ ) by tuning the drain-source voltage $V_{ds}$ of the input transistors operating in linear region. Based on fundamental analysis, $V_{ds}$ should be reduced to attenuate the nonlinear effects caused by higher-order harmonic components. This proposed transconductor circuit enables the $G_{m}$ tuning and widens the tuning range while maintaining good linearity with negligible power and area consumption. This work is then implemented into a third-order Butterworth LPF. Measurements show that with external control voltage varying from 450 mV to 550 mV, the cutoff frequency of the LPF can be continuously adjusted from 20 MHz to 80 MHz. This design is implemented in 40 nm CMOS process with 1.1 V supply voltage. The total power consumption of this work is below 2 mW with an active area of 0.0105 mm2. Its low power consumption and good area efficiency makes this LPF suitable for WBAN applications.